2010
DOI: 10.1007/s10459-010-9252-5
|View full text |Cite
|
Sign up to set email alerts
|

New graduates’ conceptions of and approaches to veterinary professional practice, and relationships to achievement during an undergraduate internship programme

Abstract: New graduate veterinarians report differing experiences of the transition to practice. Some make a rapid transition to professional autonomy while others require prolonged and extensive support from their colleagues. Factors contributing to this variation are unclear. This study used phenomenography to analyse the conceptions of and approaches to veterinary professional practice (VPP) reported by new graduates in semi-structured interviews (n = 22). Quantitative statistical analysis was used to investigate lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In one study, Dornan and others (2007) found that medical students’ own level of confidence and competency contributed to their motivation to participate in the clinical workplace. In another series of studies, Matthew and others (2010, 2011) have shown that engagement was among the behaviours that promote success in clinical practice as new veterinary graduates. Thus, the contribution of a student's engagement to the impressions formed of them by supervisors may be construct‐relevant and appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, Dornan and others (2007) found that medical students’ own level of confidence and competency contributed to their motivation to participate in the clinical workplace. In another series of studies, Matthew and others (2010, 2011) have shown that engagement was among the behaviours that promote success in clinical practice as new veterinary graduates. Thus, the contribution of a student's engagement to the impressions formed of them by supervisors may be construct‐relevant and appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Kolb (1984) and Schon (1987) both made significant theoretical contributions to how CWL was organised, taught and assessed, with the fostering of selfreflection considered to be integral to an attitude of lifelong learning. The incorporation of reflective portfolios into assessment programmes (David, Davis, Harden, Howie, Ker & Rippard, 2001) and empirical research identifying associations between reflective practices and the quality of clinical learning represent uptake of this discourse by the HSER community (Matthew, Ellis, & Taylor, 2011).…”
Section: Discourses and Trajectories Of Cwl Theory: What Has Been Stumentioning
confidence: 99%